Computed tomography findings in patients with minor head trauma presenting with a history of loss of consciousness and/or amnesia, Glasgow Coma Scale 15 and no focal neurological deficit - Singata, Chuma (Division of Radiology, 2018)
Background: South Africa is a developing country with limited resources. Currently, in our institution, patients who have suffered a minor head injury with a Glasgow Coma Scale (GCS) 15, loss of consciousness (LOC) and amnesia obtain a computed tomography (CT) scan, regardless of the cost that is incurred by the use of this limited resource. Applying recommendations in developing countries requires consideration of resource limitations and patient burden. Objective: Our objectives were twofold: 1. To determine the number of abnormalities found on routine head CTs in patients who have a history of LOC and amnesia/PTA post trauma, but with a normal mental status (GCS 15) on presentation to the trauma unit. 2. To determine the clinical value of routine CT scan of the head in patients who have suffered minor head injury with GCS 15, LOC and amnesia. Methods: The CT scan reports of 460 patients with minor head injury, GCS 15, LOC and amnesia were reviewed retrospectively in the radiology unit of Groote Schuur Hospital between the years 2012 and 2014. These patients were assessed by the trauma doctor and referred to the radiology department for a CT scan of the head. Reports had been prepared and verified by a radiology specialist or senior registrar. Results: The findings on CT were categorized as significant and insignificant. A total of 33 patient reports (7%) met the criteria of significant findings that required neurosurgical intervention. (CI 4, 7-9, 6). 320 patients (70%) had normal findings while 107 patients (23%) had insignificant findings. Conclusion: CT scan of the head in minor head injury patients with normal mental status (GCS 15) is recommended even in the face of the limited resource in view of our study results.